Intensifying Functional Task Practice to Meet Aerobic Training Guidelines in Stroke Survivors - Kelly, Liam P.; Devasahayam, Augustine J.; Chaves, Arthur R.; Wallack, Elizabeth M.; McCarthy, Jason; Basset, Fabien A.; Ploughman, Michelle (Frontiers in Physiology, 2017)
Objective: to determine whether stroke survivors could maintain workloads during functional task practice that can reach moderate levels of cardiometabolic stress (i.e. ≥ 40% oxygen uptake reserve (V̇O2R) for ≥ 20 min) without the use of ergometer-based exercise. Design: cross-sectional study using convenience sampling Setting: research laboratory in a tertiary rehabilitation hospital Participants: chronic hemiparetic stroke survivors (>6-months) who could provide consent and walk with or without assistance Intervention: a single bout of intermittent functional training (IFT). The IFT protocol lasted 30 min and involved performing impairment specific multi-joint task-oriented movements structured into circuits lasting approximately 3 min and allowing 30-45 sec recovery between circuits. The aim was to achieve an average heart rate (HR) 30-50 beats above resting without using traditional ergometer-based aerobic exercise. Outcome measures: attainment of indicators for moderate intensity aerobic exercise. Oxygen uptake (V̇O2), carbon dioxide production (V̇CO2), and HR were recorded throughout the 30 min IFT protocol. Values were reported as percentage of V̇O2R, HR reserve (HRR) and HRR calculated from predicted maximum HR (HRRpred), which were determined from a prior maximal graded exercise test. Results: Ten (3-female) chronic (38±33 months) stroke survivors (70% ischemic) with significant residual impairments (NIHSS: 3±2) and a high prevalence of comorbid conditions (80% ≥1) participated. IFT significantly increased all measures of exercise intensity compared to resting levels: V̇O2 (∆ 820 ± 290 ml min-1, p<0.001), HR (∆ 42 ± 14 bpm, p<0.001), and energy expenditure (EE; ∆ 4.0 ± 1.4 kcal min-1, p<0.001). Also, mean values for percentage of V̇O2R (62±19), HRR (55±14), and HRRpred (52±18) were significantly higher than the minimum threshold (40%) indicating achievement of moderate intensity aerobic exercise (p= 0.004, 0.016, and 0.043, respectively). Conclusion: Sufficient workloads to achieve moderate levels of cardiometabolic stress can be maintained in chronic stroke survivors using impairment-focused functional movements that are not dependent on ergometers or other specialized equipment.